Computational Modelling to Predict the Pressure Loss Coefficient of Pipe Fitting at KKTDI - Elonggo, Koghilan; Nor Salim, Nor Adrian; Taib, Ishkrizat (Progress in Aerospace and Aviation Technology, 2022)
Water pipeline system has an important role in delivering water throughout the whole community using piping system. If there is any leakages or damages in any part of the water pipeline system will not only cause problem in delivering water but also could cause cost damage and affect the daily life of the community. The main objective of this research is to investigate the flow characteristics in the pipeline at Kolej Kediaman Tun Dr. Ismail (KKTDI) and to investigate the pressure drop due effect due to leakage along the pipeline system. The second objective is to assess the CFD approaches to calculate the pressure loss coefficients. Computational Fluid Modelling (CFD) simulations used to predict the flow variables such as velocity, pressure by solving the mathematical equations describing the relationship between the flow variables. This program is used in this research to determine the pressure loss coefficients using simulations. The pressure loss coefficient of the piping system is around 33.8 to 50.4 while the average pressure loss coefficient of the plotted graph is 13.1. In conclusion, the pipeline system of KKTDI residential college is studied carefully to determine the pressure loss coefficient and the objective is achieved.